The Impact of Trace Elements on Osteoarthritis - Li, Guoyong; Cheng, Tao; Yu, Xuefeng (Frontiers in Medicine, 2021)
Osteoarthritis (OA) is a progressive degenerative disease characterized by cartilage degradation, synovial inflammation, subchondral sclerosis and osteophyte formation. It has a multifactorial etiology with potential contributions from heredity, endocrine function, abnormal mechanical load and nutrition. Of particular considerations are trace element status. Several trace elements, such as boron and magnesium are essential for normal development of the bone and joint in human. While cadmium correlates with the severity of OA. The present review focuses on the roles of trace elements (boron, cadmium, copper, iron, magnesium, manganese, selenium, zinc) in OA and explores the mechanisms by which they act.